PENGARUH PERENCANAAN ANGGARAN, KOMPETENSI PEGAWAI, REFORMASI BIROKRASI, DAN DISIPLIN KERJA TERHADAP MOTIVASI DAN PENYERAPAN ANGGARAN - Mulyanto, Kurniawan Cahyo Utomo & (Universitas Slamet Riyadi, 2014)
This study aimed to examine the effect of budget planning, employee competence, bureaucratic reform and discipline of work on motivation, and absorption. This study took a sample of 108 respondents, the unit gained budget funds within the region pay the State Treasury Office consisting of Klaten region, the census method. The data in this research will be obtained directly from the questionnaires and the answers that have been provided or the results of field observations. The data analysis using path analysis, t-test, F and R Total. Regression equation results showed that the significant effect on the budget plan units of work motivation. Competence of the employees have a significant effect on the motivation of the work force. Bureaucratic reforms have a significant effect on the motivation of the work force. Discipline significant effect on the motivation of the work unit. Budget planning significant effect on absorption. Employee competence insignificant effect on the absorption of the budget. Bureaucratic reform significantly influence absorption. Labor discipline significantly influence absorption. Motivation unit significant positive effect on absorption. The conclusion of this line of analysis suggests that the use of intervening variables in order to improve performance, to a variable budget planning, bureaucratic reform and labor discipline is not effective. The use of intervening variables motivated work force in order to increase the absorption of the budget for employee competence variable is effective. Keywords: budget planning, employee competence, bureaucratic reform, labor discipline, motivation, absorption.